2021
DOI: 10.1200/jco.2021.39.15_suppl.6506
|View full text |Cite
|
Sign up to set email alerts
|

The association of sexual orientation with cancer screening and diagnosis.

Abstract: 6506 Background: Data on heterogeneity in cancer screening and diagnosis rates among sexual minorities (SMs) is lacking. Recent studies have shown SMs are more likely to engage in risky health behavior and have decreased healthcare utilization compared to heterosexual counterparts. However, few studies have examined how sexual orientation (SO) impacts cancer screening and prevalence. We therefore investigated whether SO affects prevalent gender-specific cancer screening and prevalence, including prostate (PCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Herriges et al (1) The Legend: LBW = lesbian women and bisexual women are obesity, nulliparity, medications suppressing the ovaries, and anovulation. Risk factors such as polycystic ovarian syndrome, tamoxifen use, hypertension and diabetes mellitus, and Lynch syndrome are thought to affect the prevalence at the same rate as in heterosexual women.…”
Section: Sample Size Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Herriges et al (1) The Legend: LBW = lesbian women and bisexual women are obesity, nulliparity, medications suppressing the ovaries, and anovulation. Risk factors such as polycystic ovarian syndrome, tamoxifen use, hypertension and diabetes mellitus, and Lynch syndrome are thought to affect the prevalence at the same rate as in heterosexual women.…”
Section: Sample Size Resultsmentioning
confidence: 99%
“…(8,19) In addition, the main risk factors for cervical cancer, namely early sexual intercourse before the age of 16, polygamous sexual life, and STIs such as HPV-16 and HPV-18, [especially HPV-11 and HPV-16], are common in LBW and are reported to increase the risk of getting caught. (1,9) It is known that HPV-16 and HPV-18 are responsible for almost 70% of all cervical cancer cases. When the literature is examined, different study results related to the subject were found.…”
Section: Cervical Cancermentioning
confidence: 99%
See 3 more Smart Citations